2019
DOI: 10.1186/s12917-019-2007-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial endotoxin decreased histone H3 acetylation of bovine mammary epithelial cells and the adverse effect was suppressed by sodium butyrate

Abstract: Background In practical production, dairy cows are frequently exposed to bacterial endotoxin (lipopolysaccharide, LPS) when they are subjected to high-concentrate diets, poor hygienic environments, as well as mastitis and metritis. Histone acetylation is an important epigenetic control of DNA transcription and a higher histone acetylation is associated with facilitated transcription. LPS might reduce histone acetylation in the mammary epithelial cells, resulting in lower transcription and mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…At the same time, compared with the CON group, the relative mRNA expression of CSN1 and CSN2 significantly decreased and the relative mRNA expression of CSN3 also decreased numerically. Our previous study showed that LPS suppressed lactation-related gene expression due to reducing histones H3 acetylation by enhancing HDAC activity [16]. Taken together, our results revealed that PGN and LTA reduced histone H3 acetylation through regulating HAT and HDAC activity, which might result in lower mRNA expression of caseins.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…At the same time, compared with the CON group, the relative mRNA expression of CSN1 and CSN2 significantly decreased and the relative mRNA expression of CSN3 also decreased numerically. Our previous study showed that LPS suppressed lactation-related gene expression due to reducing histones H3 acetylation by enhancing HDAC activity [16]. Taken together, our results revealed that PGN and LTA reduced histone H3 acetylation through regulating HAT and HDAC activity, which might result in lower mRNA expression of caseins.…”
Section: Discussionsupporting
confidence: 59%
“…Our previous study showed that LPS enhanced immune responses of bovine mammary epithelial cells by decreasing DNA methylation [15]. Moreover, our other study indicated that LPS reduced histone H3 acetylation through enhancing HDAC activity, and subsequently suppressed the expression of lactation-related genes, such as acetyl coenzyme-A carboxylase 1 (ACACA), fatty acid synthase (FASN), and ribosomal protein S6 kinase 1 (S6K1) [16]. Like E. coli, S. aureus could induce bovine subclinical mastitis by regulating DNA methylation [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Persistent peripheral presence of S. aureus reduced histone H3 acetylation in rat brain tissues [ 55 ]. In addition to the direct effects of bacterial pathogens on histone acetylation, we found in our previous study that LPS (0.1 μg/mL) could suppress lactation-related gene expression through reducing histone H3 acetylation by enhancing HDAC activity in BMECs [ 39 ]. In this study, LPS (0.1 μg/mL) significantly decreased histone H3 acetylation and the expression of three caseins, which was consistent with our previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that LTA and PGN could cause the DNA hypomethylation of the key regulators of inflammatory pathways, promoting the release of a variety of inflammatory factors [37,38]. In addition, our previous studies showed that LPS, LTA, and PGN suppressed the expression of lactation-related genes of BMECs due to reducing histone H3 acetylation through regulating HAT and HDAC activity [19,39]. Thus, we speculated that co-stimulation with LPS, LTA, and PGN might have an additive effect on DNA hypomethylation and histone hypoacetylation, producing a more intense inflammatory response and decreasing casein expression to a greater degree than single stimulation of either of the PAMPs in BMECs.…”
Section: Introductionmentioning
confidence: 90%
“…Histone octamer and DNA constitute nucleosomes, which are free in the N-terminal of the nucleosome and can accept various modifications, including acetylation and deacetylation (63,64). Active histones H4 and H3 acetylate lysine residues under the action of histone acetyltransferase, which facilitates chromatin expression, while histone deacetylase acts contrary and blocks chromatin expression (65). Acetylation and deacetylation of histones are dynamic.…”
Section: Discussionmentioning
confidence: 99%